THE ROLE OF AKHLAK AQIDAH TEACHERS IN IMPROVING MORALS AT MTS AL-URWATUL WUTSQO JOMBANG - Khoulita, Ikfi (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2023)
The purpose of this study is to describe the role of the Aqidah Akhlak teacher in improving the morals of students at MTs Al-Urwatul Wutsqo Jombang, to describe the morals of students at MTs Al-Urwatul Wutsqo Jombang, to describe the supporting and inhibiting factors for moral development at MTs Al-Urwatul Wutsqo Jombang. This type of research is qualitative research with data collection techniques using observation techniques, in-depth interviews, and documentation. Data analysis starts from data reduction, data presentation, and drawing conclusions. The role of the teacher at MTs Al-urwatul wutsqo is the role of the moral creed teacher as a communicator, motivator and mentor. The communicator looks familiar to the students and the teacher. The motivator can be seen from every time the teacher always gives encouragement to do good, both ukrowi and worldly motivation in the form of praise. As a mentor, it can be seen that the teacher always reminds students, for example, if there is student misbehavior, the teacher must guide students in a good direction so that they do not deviate from Shari'a.’at-syar’adhere to Islam and motivate students not to do that again. Morals that appear are commendable morals. Examples of not exaggerating, good behavior, humble, knowledgeable, charitable, honest, true to promises, istiqamah, steadfast, courageous, patient, grateful. The supporting factors are the Madrasah environment, namely the pesantren, curriculum,. The inhibiting factors are the different backgrounds of students, the home environment of students, and the lack of awareness in students.